A comparison of the efficacy of weight-shift vs. joystick control of a robotic mobility device by infants ages 5 to 10 months. Issue 2 (15th March 2018) - Stansfield, Sharon; Dennis, Carole; Altman, Rachel; Smith, Janelle; Larin, Hélène
ABSTRACT: The onset of crawling in infants contributes to cognitive, perceptual, social, and emotional development. Conversely, infants with motor impairment that delays or prevents autonomous mobility often have associated developmental delays. Evidence suggests that providing mobility may have positive developmental outcomes, however powered wheelchairs may not be recommended for very young children, due to safety concerns and the child's level of cognitive maturity. The WeeBot is a mobility device controlled by infant weight shifting while seated; infants as young as 5 months have learned to use it. This study compares the efficacy of using the WeeBot vs. using the traditional manual joystick to control a robotic mobility device. Participants were 20 typically developing infants between 5 and 10 months who had not yet achieved independent mobility. A quasi-experimental two-group design was used: The first 10 participants recruited used the WeeBot (weight-shift); the next 10 used the joystick. Results showed that infants learned to use weight-shift control more easily and more skilfully than did infants using the joystick. The ability of infants to use the WeeBot suggests that an intuitive alternative control might allow very early powered mobility for children with disabilities, which might have implications for various aspects of their development.